A Rapid and Highly Predictive in vitro Screening Platform for Osteogenic Natural Compounds Using Human Runx2 Transcriptional Activity in Mesenchymal Stem Cells - Wang, Li-Tzu; Lee, Yu-Wei; Bai, Chyi-Huey; Chiang, Hui-Chun; Wang, Hsiu-Huan; Yen, B. Linju; Yen, Men-Luh (Frontiers in Cell and Developmental Biology, 2021)
The rapid aging of worldwide populations had led to epidemic increases in the incidence of osteoporosis (OP), but while treatments are available, high cost, adverse effects, and poor compliance continue to be significant problems. Naturally occurring plant-based compounds including phytoestrogens can be good and safe candidates to treat OP, but screening for osteogenic capacity has been difficult to achieve, largely due to the requirement of using primary osteoblasts or mesenchymal stem cells (MSCs), the progenitors of osteoblasts, to conduct time-consuming in vitro and in vivo osteogenic assay. Taking advantage of MSC osteogenic capacity and utilizing a promoter reporter assay for Runx2, the master osteogenesis transcription factor, we developed a rapid in vitro screening platform to screen osteogenic small molecules including natural plant-based compounds. We screened 8 plant-derived compounds from different families including flavonoids, polyphenolic compounds, alkaloids, and isothiocyanates for osteogenic capacity using the human RUNX2-promoter luciferase reporter (hRUNX2-luc) transduced into the mouse MSC line, C3H10T1/2, with daidzein—a well-studied osteogenic phytoestrogen—as a positive control. Classical in vitro and in vivo osteogenesis assays were performed using primary murine and human bone marrow MSCs (BMMSCs) to validate the accuracy of this rapid screening platform. Using the MSC/hRUNX2-luc screening platform, we were able not only to shorten the selection process for osteogenic compounds from 3~4 weeks to just a few days, but also simultaneously perform comparisons between multiple compounds to assess relative osteogenic potency. Predictive analyses revealed nearly absolute correlation of the MSC/hRUNX2-luc reporter platform to the in vitro classical functional assay of mineralization using murine BMMSCs. Validation using human BMMSCs with in vitro mineralization and in vivo osteogenesis assays also demonstrated nearly absolute correlation to the MSC/hRUNX2-luc reporter results. Our findings therefore demonstrate that the MSC/hRUNX2 reporter platform can accurately, rapidly and robustly screen for candidate osteogenic compounds and thus be relevant for therapeutic application in OP.